Reading Human Subjectivity In Selected Contemporary Science Fiction Texts - Ismail @ Hamdan, Shahizah (2010)

(untitled)
This study engages in a critical reading of subjectivity as portrayed in selected contemporary Science Fiction texts published in the twenty first century. The reading is concerned with investigating the futurist portrayals of human subjectivity and their interfacing with technological advancements. In the context of this study, “subjectivity” is used interchangeably with “identity” and “the sense of self”. All three concepts – subjectivity, identity and the sense of self - signify human social constructs and consciousness. The concepts reflect human existence in constant negotiation with the environment in connection to explicit and implicit details related to embodiment and ideology. The reading therefore examines subjectivity within these two dimensions – embodiment and ideology. Within the embodiment dimension, whilst presupposing that the mind and body are two entities as exemplified by Rene Descartes, the analysis looks at how and why the mind/body, specified as the basis for human subjectivity is changed or altered with the availability of technologies. The 17th century Cartesian theory on subjectivity is adopted here to examine the presence and treatment of natural or nature-given sense of subjectivity within the futurist context of the Science Fiction texts. Nevertheless it is found that the famous Cartesian notion of “I think therefore I am”, which shows the mind as the entity that makes humans unique, becomes paradoxical within the materiality of the Science Fiction contexts. Therefore, to examine the material aspect, the reading appropriates Louis Althusser’s notion of the subject, to look into subjectivity situated within social practices that are highly influenced by technology. Althusser’s notion of the subject is utilised here because in his theorising, all subjects exist within ideological apparatuses governed by material practices and rituals. The technologically altered humans are then analysed within the framework of Donna Haraway’s cyborg imagery. This imagery suggests the end of the natural concepts of subjectivity such as in the Cartesian theorising and marks the beginning of posthumanism where subjectivity is influenced by technology thus materially imagined. As such this research finds that firstly, subjectivity, characteristically fluid and continuously being renegotiated in its contact with technology, is influenced and determined by the body be it organic and/or machine in humanity’s quest for longevity. Secondly, technology transforms human subjectivity into a notion that is predominantly material-imagined as the body becomes significantly important almost simultaneously as the mind loses its primacy. This switch is a result of the notion that the mind needs to be encapsulated by embodiment for subjectivity to be meaningful. Finally, the research finds that although cyborg imagery is predominantly portrayed in the selected texts as the prevailing future for human subjectivity, ironically the situation is still very much dictated by pure human desires driven by external material factors such as the need to overcome limitations of the body, the need to live a much longer live, the need to be physically beautiful and the need to be powerful as exemplified in the Science Fiction texts.